Resisting the Reflection: Identity in Inclusive Life History Research - Krist Bj (Disability Studies Quarterly, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:ArialMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:Arial; mso-font-charset:77; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.5pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-GB; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> This article addresses the issue of identity production and reproduction in relation to social participation of young adults with intellectual disabilities. It is based on life history research conducted in collaboration with young adults with intellectual disabilities in Iceland. The article challenges the usefulness of the intellectual disability label and examines how the participants resist the label by telling stories of competence and abilities. The article also explores the interplay of the intellectual disability label and other social categories, such as class and religion. It concludes with a call for more awareness of the effects that non-disabled professionals and researchers have on the intellectual disability identity by using a label that is grounded in a deficit understanding of disability.
Keywords: Labeling; habitus; identity; inclusive research; intersectionality